Analisis Statistik Persentase Perangkingan Nilai Akhir Siswa Sekolah Menengah Atas Negeri 4 Takengon Dengan Ms Excel - Ira Zulfa; Richasanty Septima S (Jurnal TUNAS, 2020)
Statistics is often used in various sciences (natural sciences or social sciences) and government.Even the application is often used in daily life. For example voting on choosing class leaders, quick counts, thesis materials, and others. Statistics provide ways to assess the uncertainty of drawing inductive conclusions. The data obtained in this study are discrete data obtained by calculating data in the form of integers such as the number of people who are quantitative in the form of numeric data and sourced from secondary data by citing records of written grades from the schools where the research was conducted. From this study it can be concluded that the quality measure of each school cannot only be seen from the acquisition of the highest grades because basically schools that are not superior will set a lower average value than the superior schools.